MAKNA NILAI-NILAI TOMANURUNG DALAM PENDIDIKAN KARAKTER - Yunus Yunus (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2021)
This post-chaos period is called the Tomanurung period with a character named Simpurusiang in Bugis language, "Simpurusiang" implies "a strong and unbroken binder". Because society is in a state of chaos and divorces. Because of this, they are looking for figures who can unite societies that have been divided and in chaos. Through a long search, they found the person they needed, namely a Tomanurung (the descendant) and they agreed to make him king through a "collective agreement" that is between Tomanurung and people's representatives. According to the perspective of the Luwu community, Tomanurung means a person who descends from heaven or heaven. Tomanurung did not know the news of his arrival beforehand, suddenly appeared and his presence was being awaited to fix the chaotic situation. Therefore, Tomanurung for the people of Luwu and Bugis-Makassar is generally considered a savior, unifier and continuation of royal life. So the value of human behavior in the past, which was the source of the lontaraq pappaseng script, such as adele '(fair), lempu' (honest), getteng (firm), Abbulo Sibatang.